2015
DOI: 10.2136/sssaj2014.10.0394
|View full text |Cite
|
Sign up to set email alerts
|

Birnessite‐Catalyzed Degradation of Glyphosate: A Mechanistic Study Aided by Kinetics Batch Studies and NMR Spectroscopy

Abstract: Glyphosate [N‐(phosphonomethyl) glycine] is a broad‐ spectrum systemic herbicide. Because of the ever‐increasing application of glyphosate in agricultural fields and detection of its presence in soils and environmental waters, there is a growing concern that it may potentially harm animal and human populations and the environment. In this study, we determined the mechanism and reaction pathway of birnessite‐catalyzed degradation of glyphosate by using one‐dimensional (1H, 13C, and 31P) and two‐dimensional homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 46 publications
4
36
0
Order By: Relevance
“…This 31 P NMR technique has been applied for the analysis of PMG metabolites and degradation products in only a few earlier research works [26][27][28][29][30][31][32][33]. chemicals by the consumption of contaminated water [16][17][18][19][20][21][22][23][24][25][26]. Advanced oxidation processes (AOPs) are a key technology to solve pesticide contamination problems during both water and wastewater treatment (Table 1).…”
Section: Pmgmentioning
confidence: 99%
See 2 more Smart Citations
“…This 31 P NMR technique has been applied for the analysis of PMG metabolites and degradation products in only a few earlier research works [26][27][28][29][30][31][32][33]. chemicals by the consumption of contaminated water [16][17][18][19][20][21][22][23][24][25][26]. Advanced oxidation processes (AOPs) are a key technology to solve pesticide contamination problems during both water and wastewater treatment (Table 1).…”
Section: Pmgmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) are a key technology to solve pesticide contamination problems during both water and wastewater treatment (Table 1). PMG Birnessite (Mn 4+ and Mn 3+ ) H3PO4 +Gly P + C-P x 31 P NMR [26] Birnessite (Na0.3Ca0.1K0.1)(Mn 4+ , Mn 3+ )2O4 × 1.5 H2O. Fe (III) (C2O4)n m− − Fe(C2O4)2 − and Fe(C2O4)3 3− .…”
Section: Pmgmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, also AMPA has been found in the environment (Struger et al, 2015, Paris et al, 2013. Li et al (2015) and Paudel et al, (2015) have shown GLP and AMPA chemical degradation (P2R1c and P1R2c respectively, Figure 1) catalysed by Mn ions contained in birnessite mineral ((Na0.3Ca0.1K0.1)(Mn 3+ ,Mn 4+ ) 2 O 4 •1.5H 2 O).…”
Section: Introductionmentioning
confidence: 99%
“…This, though, also shows that glyphosate immediately degrades to AMPA within the first 2h after applying glyphosate (average time between sampling and freezing the samples). Paudel et al (2015) also reported that the majority of degradation products of glyphosate are formed within 1 min of reaction. Although the results on the formation fraction of AMPA (ffA) need to be treated with care for reasons already described in section 2.3.2, the percentage of glyphosate being degraded to AMPA also seems to be strongly influenced by temperature.…”
Section: Ampa Formation and Decaymentioning
confidence: 94%